2010
DOI: 10.18832/kp2010015
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of evaluation of drought tolerance in barley.

Abstract: Šlechtění odrůd tolerantních vůči suchu je stále důležitější z hlediska zlepšení výnosů a zdravotního stavu rostlin zvláště u hospodářsky významných plodin. Je založeno na hodnocení a účinné selekci tolerantních genotypů. Hodnocení citlivosti rostlin vůči suchu však není jednoduché, vzhledem ke komplexnímu charakteru této vlastnosti. Cílem této práce bylo porovnat stresové reakce pěti různě citlivých genotypů ječmene (Tadmor, Malz, Amulet, Bojos a Jersey) vystavených stresu suchem pomocí molekulárně biologické… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This was proven by its high osmotic adjustment (Teulat et al, 1997b), good water use effi ciency (Teulat et al, 2001;Mikulková et al, 2009) and a high relative expression of some Dhn genes (Mikulková et al, 2009;Holková et al, 2010). The results of our experiments suggest that the adaptation of Tadmor may be based on its higher WUE even in optimal conditions and relatively low endogenous ABA concentration together with its enhanced sensitivity to ABA.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…This was proven by its high osmotic adjustment (Teulat et al, 1997b), good water use effi ciency (Teulat et al, 2001;Mikulková et al, 2009) and a high relative expression of some Dhn genes (Mikulková et al, 2009;Holková et al, 2010). The results of our experiments suggest that the adaptation of Tadmor may be based on its higher WUE even in optimal conditions and relatively low endogenous ABA concentration together with its enhanced sensitivity to ABA.…”
Section: Resultsmentioning
confidence: 60%
“…The moderately droughtsensitive cultivar Malz showed a noticeable increase of Dhn4 gene expression up to 3 days of ABA treatment and the drought-sensitive Jersey showed the lowest relative expression level of this gene. In our previous studies a low activity of protective Dhn genes was observed in the Jersey cultivar under various stress conditions (Mikulková et al, 2009;Holková et al, 2010). Park et al (2006) also described a faster activation and a higher fi nal expression level of the Dhn4 gene in drought-tolerant genotypes of barley.…”
Section: Resultsmentioning
confidence: 86%